Fabrication of β-Ni(OH)2 Particles by Alkaline Etching Layered Double Hydroxides Precursor for Supercapacitor - Chen, Lumei; Yang, Xiaotong; Tian, Ye; Wang, Yiping; Zhao, Xuhui; Lei, Xiaodong; Zhang, Fazhi (Frontiers in Energy Research, 2022)
We report facile preparation of β-Ni(OH)2 particles by etching a NiAl-layered double hydroxides (NiAl-LDHs) precursor with KOH solution. The amphoteric Al3+ ions in LDHs crystal were selectively dissolved out by KOH solution and LDHs crystals were proposed to be in situ topologically transformed to form β-Ni(OH)2. Alkaline concentration has a great influence on structure, morphology, specific surface area and porous structure of the resulting samples. Compared to LDHs precursor and β-Ni(OH)2 prepared by precipitation reaction, the sample etched in 10 M KOH solution has enhanced specific capacitance (829 F/g at 1 A/g), high rate capability (capacitance retention 57.3% with current density 8 A/g), and good charge/discharge stability. We suggested that the high accessible specific surface area and appropriate porous structure, which is conducive to full contact between active material and electrolyte, can improve the utilization rate of the active material to increase rate capacity of the 10 M KOH-etched sample.